Kansas farm management association dairy cow herd enterprise management analysis - F. D. DeLano; Michael R. Langemeier (Kansas Agricultural Experiment Station Research Reports, 1993)
Actual dairy cow herd enterprise records from Kansas Farm Management Association farms over the past 4 years have shown an increase in returns over variable costs from 17,900 to 23,300 per farm for a 100-cow dairy herd in favor of herds with higher milk-producing cows. Cost per hundred weight of milk produced per cow decreased for the higher-producing herds compared with lower-producing herds, even though total cost per cow increased. In 1992, for every extra 1.00 spent on feed and other variable costs, the higher producing herds earned 1.71. This was a 71% return per dollar invested.; Dairy Day, 1993, Kansas State University, Manhattan, KS, 1993;
Keywords: Dairy Day; 1993; Kansas Agricultural Experiment Station contribution; no. 94-149-S; Report of progress (Kansas Agricultural Experiment Station); 694; Dairy; Economics; Management